Comparison of Gene Expression Responses in the Small Intestine of Mice Following Exposure to 3 Carcinogens Using the S1500+ Gene Set Informs a Potential Common Adverse Outcome Pathway. (October 2019) - Chappell, Grace A.; Rager, Julia E.; Wolf, Jeffrey; Babic, Milos; LeBlanc, Kyle J.; Ring, Caroline L.; Harris, Mark A.; Thompson, Chad M.
Carcinogenesis of the small intestine is rare in humans and rodents. Oral exposure to hexavalent chromium (Cr(VI)) and the fungicides captan and folpet induce intestinal carcinogenesis in mice. Previously ( Toxicol Pathol. 330:48-52), we showed that B6C3F1 mice exposed to carcinogenic concentrations of Cr(VI), captan, or folpet for 28 days exhibited similar histopathological responses including villus enterocyte cytotoxicity and regenerative crypt epithelial hyperplasia. Herein, we analyze transcriptomic responses from formalin-fixed, paraffin-embedded duodenal sections from the aforementioned study. TempO-Seq technology and the S1500+ gene set were used to analyze transcription responses. Transcriptional responses were similar between all 3 agents; gene-level comparison identified 126/546 (23%) differentially expressed genes altered in the same direction, with a total of 25 upregulated pathways. These changes were related to cellular metabolism, stress, inflammatory/immune cell response, and cell proliferation, including upregulation in hypoxia inducible factor 1 (HIF-1) and activator protein 1 (AP1) signaling pathways, which have also been shown to be related to intestinal injury and angiogenesis/carcinogenesis. The similar molecular-, cellular-, and tissue-level changes induced by these 3 carcinogens can be informative for the development of an adverse outcome pathway for intestinal cancer.